O pensamento teórico na educação física escolar - Santos, Adnelson Araujo dos (2021)
This work intended to analyze the formation of theoretical thinking in school physical education effective from the cultural-historical theory, specifically in V. V. Davídov´s theory of developmental teaching and the perspective of critical-overcoming. The Thesis defended in the work is that the theorical assumptions of study activity and developmental teaching provide didactic-pedagogical tools for the formation of theoretical thinking in physical education at schools from the early years in elementary schools. It follows the theoretical-methodological reference of dialectical materialism to analyze: a) Brazilian scientific production based on the critical-surpassing perspective and Davídov´s developmental teaching.; b) the origin and development of the theory of concept formation as an essential general element in the formation of theoretical thinking; c) the activity theory and the involvement of periodization of psychic development of the organization of physical education teaching; d) the theory of study activity and study tasks in the physical education teaching aim to develop theoretical thinking from the first years of elementary school; e) the formative experiment as a unit between research and teaching in a developmental perspective; f) didactic-pedagogical experiences in the teaching of Brazilian Physical Education with a view to developing theoretical thinking. It shows that there is a growing increase in Brazilian scientific production which analyzes the formation of theoretical thinking in physical education, particularly in the period from 2010 to 2020, however, there is no elaboration of researchers from the North region or linked to institutions in that region in Brazil. It shows that the essential general element for the formation of theoretical thinking is the creation of theoretical concepts and it indicates the different research trials that support the debate of the perspective of critical-overcoming and developmental teaching. It also demonstrates that the pedagogical-didactic experiences in the teaching of physical education at school did not develop formative experiments in the light of what is recommended by developmental teaching, but relatively isolated, prompt and restricted didactic actions. In conclusion, the theoretical foundations of the study activity, dominant activity at school age and the developmental education have essential elements for the school education organization that allow the appropriation of theoretical knowledge.